2016
DOI: 10.1093/hmg/ddv636
|View full text |Cite
|
Sign up to set email alerts
|

Gene network and familial analyses uncover a gene network involving Tbx5/Osr1/Pcsk6 interaction in the second heart field for atrial septation

Abstract: Atrial septal defects (ASDs) are a common human congenital heart disease (CHD) that can be induced by genetic abnormalities. Our previous studies have demonstrated a genetic interaction between Tbx5 and Osr1 in the second heart field (SHF) for atrial septation. We hypothesized that Osr1 and Tbx5 share a common signaling networking and downstream targets for atrial septation. To identify this molecular networks, we acquired the RNA-Seq transcriptome data from the posterior SHF of wild-type, Tbx5(+/) (-), Osr1(+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…So far OSR1 has been associated with congenital kidney and heart defects in both animal models (Wang et al 2005) and in human patients (Zhang et al 2016). Our results suggest Osr1 is a potential gene associated with human respiratory and digestive diseases as well, serving as another screening candidate and potential treatment target in humans with congenital respiratory and digestive defects.…”
Section: Discussionmentioning
confidence: 99%
“…So far OSR1 has been associated with congenital kidney and heart defects in both animal models (Wang et al 2005) and in human patients (Zhang et al 2016). Our results suggest Osr1 is a potential gene associated with human respiratory and digestive diseases as well, serving as another screening candidate and potential treatment target in humans with congenital respiratory and digestive defects.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to differentiate may lead to AVSDs . Molecular mechanisms controlling atrium and DMP development include PDGF signaling, BMP, Tbx5, Osr1, and FoxF1 . Tissue‐specific deletion of Smoothened resulted in compromised DMP formation, AVDs, reduced proliferation, and diminished Wnt/β‐catenin signaling .…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
“…73,219 Molecular mechanisms controlling atrium and DMP development include PDGF signaling, 171,218 BMP, Tbx5, Osr1, and FoxF1. 220,221 Tissue-specific deletion of Smoothened resulted in compromised DMP formation, AVDs, reduced proliferation, and diminished Wnt/β-catenin signaling. 216 In humans, ASDs account for about 9% of more 9700 patients, which is far less than the 69% of children with OFT malformations.…”
Section: Malformations At the Inflow Tract Of The Heartmentioning
confidence: 99%
“…For example, genetic inducible fate mapping (GIFM) has shown that the entire atrial septum, including the DMP, derives from the SHF (32). Furthermore, the molecular requirement for the Hedgehog (Hh) and BMP signaling pathways and the Tbx5 cardiogenic transcription factor for AV septation reside in the SHF (32)(33)(34)(35)(36)(37)(38). These observations lay the groundwork for investigating the molecular pathways required for atrial septum formation in SHF cardiac progenitor cells.…”
mentioning
confidence: 99%